2002
DOI: 10.1063/1.1495537
|View full text |Cite
|
Sign up to set email alerts
|

A lower bound on the quantum capacity of channels with correlated errors

Abstract: The highest fidelity of quantum error-correcting codes of length n and rate R is proven to be lower bounded by 1 − exp[−nE(R) + o(n)] for some function E(R) on noisy quantum channels that are subject to not necessarily independent errors. The E(R) is positive below some threshold R 0 , which implies R 0 is a lower bound on the quantum capacity. This work is an extension of the author's previous works [M. Hamada, Phys. Rev. A, 65, 052305 (2002), e-Print quant-ph/0109114, LANL, 2001, and M. Hamada, e-Print quant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…Extending this work's result to the case of channels with memory of a Markovian nature is possible if second-order (or higher-order) types are used instead of the usual types [52]. It may be also interesting to ask whether the present approach will help us obtain bounds or improve the known ones for Gaussian quantum channels already discussed in the literature [53], [54], [55].…”
Section: Discussionmentioning
confidence: 96%
“…Extending this work's result to the case of channels with memory of a Markovian nature is possible if second-order (or higher-order) types are used instead of the usual types [52]. It may be also interesting to ask whether the present approach will help us obtain bounds or improve the known ones for Gaussian quantum channels already discussed in the literature [53], [54], [55].…”
Section: Discussionmentioning
confidence: 96%
“…[18,19] and references therein). A Lindbladian approach to memory channels has been taken by Daffer et al [20,21].…”
Section: B Model Systems and Related Workmentioning
confidence: 99%
“…Correlated qubit channels were originally studied in terms of classical information transmission and it was shown that for certain ranges of the correlation strengths the use of entanglement allows one to enhance the amount of transmitted information along the channel [7]. Quantum memory (or correlated) channels then attracted growing attention, and interesting new features emerged by modeling of relevant physical examples, including depolarizing channels [8], Pauli channels [9][10][11], dephasing channels [12][13][14][15][16], amplitude damping channels [17,18], Gaussian channels [19], lossy bosonic channels [20,21], spin chains [22], collision models [23] and a micro-maser model [24] (for a recent review on quantum channels with memory effects see Ref. [25]).…”
Section: Introductionmentioning
confidence: 99%